P583 Efficacy of vedolizumab (VDZ) by disease extension in ulcerative colitis. (16th January 2018) - Michetti, P; Braegger, F; Kempf, C; Allez, M
Abstract: Background: Disease extension in ulcerative colitis (UC) is one of the major factors determining long-term prognosis. Patients with extensive colitis have more frequent complications, extraintestinal manifestations and systemic symptoms, need more immunosuppressive and surgical therapies, and have a greater cancer risk. It is, therefore, important to determine whether the efficacy of available treatments is affected by disease extension. Results of the pivotal GEMINI 1 trial suggested that VDZ, a humanised monoclonal α4β7 antibody approved for UC, is efficacious regardless of disease extension. Methods: A post hoc analysis was conducted on the maintenance phase intent-to-treat (mITT) population of the GEMINI 1 trial to further examine VDZ efficacy by disease extension and any potential confounding factors. The following efficacy outcomes were assessed at Week 52 by disease extension (proctosigmoiditis, left-sided colitis, extensive colitis, pancolitis): clinical response (reduction in complete Mayo score ≥3 points and ≥30% reduction from baseline with a decrease in rectal bleeding subscore ≥1 point, or absolute rectal bleeding score of ≤1 point); clinical remission (Mayo score ≤2 points and no individual subscore >1); corticosteroid (CS)-free remission in patients receiving CSs at baseline; and mucosal healing (Mayo endoscopic subscore ≤1). Logistic regression assessed the impact of disease extension (extensive colitis vs. pancolitis, left-sided colitis vs. pancolitis, proctosigmoiditis vs. pancolitis), prior anti-TNFα therapy, prior CS exposure, concomitant immunomodulator use and baseline calprotectin on clinical response, clinical remission and mucosal healing at Week 52. Results: The mITT population comprised 373 patients (proctosigmoiditis: 41; left-sided colitis: 149; extensive colitis: 45; pancolitis: 138). VDZ improved all four efficacy measures vs. placebo at both study dose regimens (every 4 weeks or every 8 weeks) across all disease extension subgroups. None of the potential confounding factors included in the logistic regression analysis were found to be significant. Conclusions: VDZ (both dosing regimens) was more efficacious than placebo at improving disease activity in patients with UC. Disease extension, prior and/or concomitant therapy, and calprotectin levels did not impact this result. A limitation of this analysis was the small patient number in each subgroup; larger studies are required to identify any statistically significant differences.